2004
DOI: 10.1002/bjs.4461
|View full text |Cite
|
Sign up to set email alerts
|

Use of the time–signal intensity curve from dynamic magnetic resonance imaging to evaluate remnant pancreatic fibrosis after pancreaticojejunostomy in patients undergoing pancreaticoduodenectomy

Abstract: The TIC obtained from dynamic MRI is a reliable indicator of fibrosis in the remnant pancreas after pancreaticoduodenectomy. Use of a DMA was associated with a lower risk of pancreatic fibrosis 1-3 years after surgery than a PJSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Park et al (25) observed that high perfusion in pancreatic cancer detected on DCE-CT was associated with increased response to chemoradiotherapy. Also, the role of DCE magnetic resonance imaging has evolved in the field of perfusion imaging, and several groups have used it in evaluating the perfusion of benign and malignant pancreatic lesions (10,(26)(27)(28). Nevertheless, [ 15 O]H 2 O PET has been studied more extensively than either DCE-CT or magnetic resonance imaging, and is regarded by some authors as a gold standard in perfusion imaging (15).…”
Section: O]h 2 O and [mentioning
confidence: 99%
“…Park et al (25) observed that high perfusion in pancreatic cancer detected on DCE-CT was associated with increased response to chemoradiotherapy. Also, the role of DCE magnetic resonance imaging has evolved in the field of perfusion imaging, and several groups have used it in evaluating the perfusion of benign and malignant pancreatic lesions (10,(26)(27)(28). Nevertheless, [ 15 O]H 2 O PET has been studied more extensively than either DCE-CT or magnetic resonance imaging, and is regarded by some authors as a gold standard in perfusion imaging (15).…”
Section: O]h 2 O and [mentioning
confidence: 99%
“…Dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) has been used to assess pancreatic blood flow in healthy volunteers and patients. However, this technique requires the injection of a gadolinium-based contrast agent from which the first pass is measured and quantified for perfusion, 7,8 which again limits repeat measures. Arterial spin labeling (ASL) has been used previously to measure perfusion in the pancreas 9,10 as well as several other abdominal organs [11][12][13] without administration of contrast agent, thus allowing for repeated measures and enables the assessment of temporal changes in pancreatic perfusion, without the risks associated with intravenous contrast agents.…”
mentioning
confidence: 99%
“…The pancreatic TICs were calculated and plotted as the percentage increase in the SI of the pancreas, according to the enhancement formula (SI post − SI pre )/SI pre × 100, where SI pre and SI post represent the pre-and post-contrast (25 s, and 1, 2, and 3 min after a rapid bolus injection of contrast) SIs of the pancreas obtained from dynamic contrast-enhanced T1-weighted MRI, respectively. The pancreatic TICs can be categorized into three types; type I shows a rapid rise to a peak, followed by a rapid decline, and types II and III show a slow rise to a peak, followed by a slow decline or a plateau [46]. In patients who underwent PD, the pancreatic TIC analyses yielded several findings.…”
Section: Mri Studiesmentioning
confidence: 98%
“…Dynamic MRI-based perfusion characteristics of the pancreas displayed as the time-signal intensity curve (TIC) have enabled the precise assessment of the histological degree of pancreatic fibrosis in association with the occurrence of POPF after PD [18,46]. The pancreatic TICs were calculated and plotted as the percentage increase in the SI of the pancreas, according to the enhancement formula (SI post − SI pre )/SI pre × 100, where SI pre and SI post represent the pre-and post-contrast (25 s, and 1, 2, and 3 min after a rapid bolus injection of contrast) SIs of the pancreas obtained from dynamic contrast-enhanced T1-weighted MRI, respectively.…”
Section: Mri Studiesmentioning
confidence: 99%
See 1 more Smart Citation